Research on source impedance characteristics of an axial piston pump - Takayoshi ICHIYANAGI; Takao NISHIUMI (Nihon Kikai Gakkai ronbunshu, 2019)
The fluid borne-vibration generated from a hydraulic pump is known to be one of drawbacks in hydraulic systems. In order to decrease the noise and vibration effectively, the simulation tool to predict the pressure ripple at an arbitrary point in the hydraulic circuit must be used at a design stage. Therefore, accurate mathematical models for hydraulic components is required for such simulation. In this research, the target is set to develop a precise mathematical model for the source impedance characteristics of an axial piston pump. In the past research, the simple approximation models have been already developed to be able to express the source impedance characteristics. These models need the parameter identification for the dimension of discharge passageway by the experimental acquired source impedance. Hence, the models can not be used as a design purpose. In this report, the theoretical investigations which consider shapes and dimensions of a discharge passageway inside the pump, as well as the pump chambers with discharge process, are conducted and compared with the experimental results. It was found that the source impedance of axial piston pump can be modeled by the distributed parameter pipe model which takes into account all pump chambers connecting the discharge port.